Vegetation Mapping and Analysis of Its Spatial Distribution in Typical Water Level Fluctuating Zone of Xiaowan Reservoir on Lantsang River in Drought Year - Jiang Weiwei; Zhu Song; Xiao Henglin (Shuitu baochi tongbao)
[Objective] The natural restoration of vegetation in the water level fluctuating zone (WLFZ) of the Xiaowan Reservoir on Lantsang River during a drought year were investigated to provide background information and a reference for studies related to the restoration and maintenance of vegetation in the area. [Methods] Based on a fixed sample site survey in a typical area of WLFZ in 2019, a drought year reset survey was conducted in July 2020 using a combination of unmaned aerial vehicle (UAV) remote sensing, GNSS positioning, and GIS spatial analysis to map the distribution of vegetation in WLFZ in the study area; quantitatively portray the species composition, area, cover, and distribution characteristics along a topographic gradient of vegetation in WLFZ in the drought year; and conduct a comparative analysis with the non-drought year of 2019. [Results] A total of 14 species of plants were counted, all of which were annual or perennial herbs. Cynodon dactylon, Polygonum plebeium, Epilobium hirsutum, and Ageratum conyzoides were the dominant species, accounting for 85.62%, 4.22%, 3.72%, and 3.12% of the total vegetation area, respectively. The proportions of C. dactylon in WLFZ were 50.21%, 9.94%, and 39.85% in sections H, M, and L (high, medium, and low), respectively; 95.53% of E. hirsutum was distributed in section H; 54.48% of A. conyzoides was distributed in section M; and 87.22% of P. plebeium was distributed in sections M and L. Most plants preferred to grow on gentle slopes below 25° in WLFZ, while E. hirsutum covered well on slopes less than 60°. Vegetation in WLFZ was influenced by topographic factors: distance to the nearest neighboring water body > elevation > slope > aspect. Drought resulted in an annual degradation of 59.75% of the vegetation, concentrated in the middle and lower parts of WLFZ, where a large amount of P. plebeium withered. [Conclusion] Vegetation recovery was more stable in the upper half of the zone than in the lower half, and the dominant species were significantly more stable than the non-dominant species, with C. dactylon and P. plebeium being more tolerant of flooding, while C. dactylon showed greater drought tolerance and recovery stability than P. plebeium. Drought stress and inundation stress had significant effects on the spatial distribution of vegetation in WLFZ. In drought years, drought stress had a slightly greater effect than inundation stress.